What's Meat Got to Do with It? Some Considerations for Ecologizing Education with Respect to Diet. Issue 4 (8th March 2018) - Rice, Suzanne
Abstract: Even in a society of meat‐eaters such as the United States, when diet is addressed in school at all, it is widely treated as matter of personal choice, the consequences of which are borne by individual consumers. Overlooked are myriad connections involved in human diet and the implications of consumption for other entities. In the first part of this essay, Suzanne Rice discusses ways in which diet, particularly meat‐eating, is connected to animal suffering, environmental harms including climate change and pollution, and risks to the health of agricultural workers and consumers. In the second part, she discusses ways in which education might be "ecologized" in efforts to help students gain insight into such connections. There are many ways to ecologize education, but regardless of how teachers proceed, they are likely to encounter not only simple ignorance, relatively unproblematic gaps in students' knowledge linked to youth and inexperience, but also willful ignorance, more problematic gaps linked to avoidance, manipulation, or rejection of evidence perceived as threatening.